Adolescents in the United States can identify familiar foods at the time of consumption and when prompted with an image 14 h postprandial, but poorly estimate portions - Schap, T.; Six, B.; Delp, E.; Ebert, D.; Kerr, Deborah; Boushey, C. (2011)
Objective To evaluate adolescents- abilities to identify foods and estimate the portion size of foods consumed in order to inform development of the mobile telephone food record (mpFR).Design Data were collected from two samples of adolescents (11-18 years). Adolescents in sample 1 participated in one lunch (n 63) and fifty-five of the sixty-three adolescents (87 %) returned for breakfast the next morning. Sample 2 volunteers received all meals and snacks for a 24 h period. At mealtime, sample 1 participants were asked to write down the names of the foods. Sample 2 participants identified foods in an image of their meal 10-14 h postprandial. Adolescents in sample 2 also estimated portion sizes of their breakfast foods and snacks.Results Sample 1 identified thirty of the thirty-eight food items correctly, and of the misidentified foods all were identified within the correct major food group. For sample 2, eleven of the thirteen food items were identified correctly 100 % of the time. Half of the breakfast and snack foods had at least one portion size estimate within 10 % of the true amount using a variety of measurement descriptors.Conclusions The results provide evidence that adolescents can correctly identify familiar foods and they can look at an image of their meal and identify the foods in the image up to 14·5 h postprandial. The results of the present study not only inform the development of the mpFR but also provide strong evidence of the use of digital images of eating occasions in research and clinical settings. © 2011 The Authors.